INTEGRASI NUMERIK TANPA ERROR UNTUK FUNGSI-FUNGSI TERTENTU - Irma Silpia; Syamsudhuha '; Musraini M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses integration techniques based on the behavior of the integrand of certain functions, which is a review of a part of the article written by Clegg, D.B. and Richmond, A. N. [International of Mathematical Education in Science and Technology. 18: 4, 519-525 (1987)]. For certain functions which satisfy the properties of the symmetry behavior of the function, integral value obtained by this technique is exact despite the methods used are the midpoint method, trapezoidal method, Simpson’s method, and Gauss quadrature rules for two points.